The Dialogue of Cultures and Education: Interconnection, Perspectives and Challenges (MMIT Proceedings, 2024)
In this thesis, the author highlights the interconnection between intercultural dialogue and education, elucidating various aspects of the theory of intercultural learning. Additionally, the author analyzes various challenges and threats facing the theory of intercultural education, and explores different trends in the development of the education system. According to the author's viewpoint, in the future, the theory of intercultural learning will undergo various changes, with a strengthened trend towards inclusivity.